2009
DOI: 10.1292/jvms.71.275
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Methimazole on the Onset of Type 2 Diabetes in Leptin Receptor-Deficient Rats

Abstract: We investigated the effects of methimazole, an anti-thyroid drug, on the onset of type 2 diabetes in Zucker diabetic fatty (ZDF) rats. For this, 0.03% methimazole was administered to 7-week-old, pre-diabetic ZDF rats in drinking water for 5 weeks and the animals were sacrificed at 12 weeks of age. Methimazole treatment to ZDF rats significantly reduced blood glucose levels, food intake, body weight, and serum T3 levels. Hepatocytes in ZDF-methi rats were more densely stained with eosin than those in ZDF rats b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…This result was supported by previous studies that showed that hypothyroidism compensated for insulin resistance by decreasing hepatic glucose output and insulin requirements in glucose regulation [33,34]. In addition, we previously reported that hypothyroidism delayed the onset of the diabetic phenotype and alleviated the reduction of hippocampal cell proliferation and neuronal progenitors [35,36]. In in vitro cell culture and in vivo studies, the overexpression of hippocampal CB and PV reduced calcium-induced cell death [37,38].…”
Section: Discussionsupporting
confidence: 80%
“…This result was supported by previous studies that showed that hypothyroidism compensated for insulin resistance by decreasing hepatic glucose output and insulin requirements in glucose regulation [33,34]. In addition, we previously reported that hypothyroidism delayed the onset of the diabetic phenotype and alleviated the reduction of hippocampal cell proliferation and neuronal progenitors [35,36]. In in vitro cell culture and in vivo studies, the overexpression of hippocampal CB and PV reduced calcium-induced cell death [37,38].…”
Section: Discussionsupporting
confidence: 80%
“…These results are in agreement with many other publications. Hwang et al (2009) andYi et al (2010) found that Serum T4 levels were significantly increased while serum total and free T3 levels were decreased in rat models of type 2 diabetes (Zucker diabetic fatty rats). Johnson (2006) reported that typical changes in poorly controlled diabetes include low serum T3 levels due to impaired extrathyroidal T4-to T3 conversion.…”
Section: Discussionmentioning
confidence: 99%
“…Hibbe, Kiesel, Kolb-Bachofen, and Kolb (1991) found that methimazole treatment did not potentiate diabetes induced by a single high dose of streptozotocin but it aggravated multiple lowdose streptozotocin-induced diabetes. Hwang et al (2009) suggested that methimazole-induced hypothyroidism may delay the onset of type 2 diabetes and thyroid hormones may be necessary for the onset of diabetes. Continuous with these literatures, the present study was conducted to assess the interaction of streptozotocin-induced diabetes and methimazole-induced hypothyroidism in albino rats.…”
mentioning
confidence: 99%
“…Although there are reports about the effects of hypothyroidism in the type 1 (Hibbe et al, 1991) and type 2 diabetic models (Matsushita et al, 2005; Tamura et al, 2005; Hwang et al, 2009), no studies have been reported about the effects of hypothyroidism in type 2 diabetic model on cell proliferation and neuroblast differentiation. In the present study, we investigated the consequences of adult-onset hypothyroidism in diabetic rats using methimazole, an anti-thyroid drug, which has been used in the management of hyperthyroid patients (Cooper 2005).…”
Section: Introductionmentioning
confidence: 99%